Avaliação da precisão do controle do limite apical de instrumentação proporcionada por localizadores eletrônicos foraminais híbridos na desobturação durante o retratamento - Frota, Luciana Maria Arcanjo (2024)
The crucial role of electronic apex locators (EFLs) in determining the apical limit during instrumentation has prompted the search for a deeper understanding of these devices in Endodontics. Thus, the present study aimed to evaluate the accuracy of a hybrid device (EFL + motor) in correctly determining the apical limit of instrumentation. An ex vivo study was conducted to assess the accuracy and reliability of the apex location during endodontic retreatment using Root ZX II (RZX), Tri Auto ZX2 (TRZX), and VDW Gold (VDW) devices in rotary motion, with the apical foramen (AF) as the limit (0.0). Thirtysix mesial canals of lower molars underwent a standardized access cavity preparation and AF length setting (150 μm) followed by chemo-mechanical preparation with WaveOne Gold Small instruments (#20/.07), obturation (gutta-percha + AH Plus), and storage in an incubator. After 21 days, the teeth were randomly divided into three groups (n = 12) based on the device used. Debridement was performed in a coronal-to-apical direction using the D1-D2-D3 instruments of the Protaper Universal Retreatment system, with the last instrument used until reaching the AF. A 2.5% NaOCl solution was used as an auxiliary irrigant. Before using the last instrument, the apices of the teeth were immersed in alginate, and the previously calibrated auto-stop function of the hybrid devices ensured that instrument rotation would stop upon reaching the desired apical limit. Subsequently, with the instrument fixed in the canal, the tooth was taken to a micro-computed tomography (micro CT) scanner to determine the distance between the instrument tip and the AF. Positive and negative values were recorded for readings beyond and short of the AF. respectively. Based on the absolute and mean error values generated by the devices and considering the non-parametric nature of the data, the results were subjected to the Kruskal-Wallis test, followed by post hoc pairwise comparisons with a significance level of 5%. No significant differences were observed among the tested hybrid devices. The measured accuracy values were 91.70% (RZX), 91.70% (VDW), and 63.63% (TRZX), with a tolerance level of ±0.5 mm. However, TRZX exhibited the highest number of readings beyond the AF distance compared to the other tested devices. In conclusion, under the conditions of this study, all devices were effective in maintaining the apical limit of instrumentation during endodontic retreatment.